Newer generation straight humeral nails allow faster bone healing and better functional outcome at mid-term - Fabrizio Mocini; Giuseppe Rovere; Domenico De Mauro; Edoardo Giovannetti De Sanctis; Amarildo Smakaj; Giulio Maccauro; Francesco Liuzza (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Purpose Although proximal and diaphyseal humerus fractures are frequent, the optimal management remains controversial. Antegrade nailing prevents further damage to the soft tissues and to the vascularization, but it has been associated with postoperative shoulder pain and dysfunction. During the latest years a straight nail design was developed to minimize these problems. Methods A total of 243 patients who had undergone surgery for antegrade intramedullary humeral nailing between January 2013 and July 2018 in A. Gemelli Trauma Center were divided into two groups according to the nail design used: straight nail group (S-group) and curvilinear nail group (C-group). Clinical data were collected using assessment forms (SF12-v2, Quick-DASH, ASES and Constant-Murley). Radiographic bone healing was assessed with RUST score at 30, 90 and 180 days after surgery. Results The S-group was made up of 128 patients with a mean age of 59 ± 19 (range 18–97) and a mean follow-up of 46 ± 9 months. The C-group was made up of 115 patients with a mean age of 53 ± 16 (range 18–88) and a mean follow-up of 51 ± 8 months. The S-group had a mental component summary (MCS) score of 54.3 ± 7.7 and a physical component summary (PCS) score of 46 ± 10.2, the C-group had a MCS score of 50.9 ± 8.4 and a PCS score of 44.1 ± 7.4. Quick-DASH and ASES were respectively 18.8 ± 4.3 and 78.6 ± 8.2 in the S-group, 28.3 ± 11.6 and 72.1 ± 13.5 in the C-group with statistical significance. Constant-Murley score was 73.9 ± 9.1 in the S-group (76% of the contralateral healthy side) and 69.4 ± 10.4 in the C-group (73% of the contralateral healthy side). The radiographic union score in the S-group was 4.1 ± 0.3 at 30 days after surgery, 7 ± 0.8 at 90 days and 10 ± 1.2 at 180 days, while in the C-group it was 4.2 ± 0.4 at 30 days, 6.4 ± 0.7 at 90 days and 9 ± 0.9 at 180 days. Conclusion Newer generation straight nails allow a faster bone healing and better functional outcome at mid-term follow up. Level of evidence III.